Issue targeted topic - Paralympic athletes (ASPETAR Sports Medicine Journal, 2018)
Markus Rehm Concussion in Para Sport (J. Kissick et al) The Female Para Athlete (Y. A. Tukali-Wosornu et al) Sports Nutrition in Para Athletes Determining energy requirements (E. Broad et al) Principles of Injury Prevention in the Para Athlete (N. Webborn et al) Unique Anti-Doping and Therapeutic Use Exemption Considerations for the Paralympic Athlete (M. N. Fedoruk et al) Technology in Para Sport: Where Have We Come From and Where Are We Going? The example of world para swimming classification (B. Burkett et al) The athlete with spinal cord injury (J. Lexell) The athlete with limb deficiency (S. E. Willick) The athlete with visual impairment (C. Winckler et al) The athlete with cerebral palsy. Challenges for the team physician (P. Runciman et al) Sports cardiology. Challenges for the team physician (B. G. Toresdahl et al)